Aktifitas Inhibitor Alpha-Glukosidase Bakteri Endofit PR-3 yang Diisolasi dari Tanaman Pare (momordica charantia) - Pujiyanto, Sri -; Ferniah, Rejeki Siti (Bioma : Berkala Ilmiah Biologi, 2010)
Some traditional medicinal plants are known to have efficacy as a medicine for diabetes. Active compoundsproduced by a plant can be derived from endophytic microbes that live in these plants. One way diabetes drugs workis to prevent digestion of complex carbohydrates into glucose so that glucose intake is reduced. Alpha-glucosidaseinhibitor is a compound that can prevent the digestion of carbohydrates, especially starch into glucose. This studyaimed to test the inhibitory activity of alpha gluosidase PR-3 isolate, an endophytic bacteria from Momordicacharantia. The results showed that the crude extract (supernatant) from PR-3 has the capability of the enzyme alphaglucosidase inhibition that is equal to 61.2% compared with positive control compound acarbose 1 mg / ml. Theresults also showed that the use of maltose as carbon source produce the highest an alpha glucosidase inhibitor(54,97%), followed by the starch (47.77%), glucose (31.97%), fructose (44.14%) and sucrose (27.7%).